Orthopedic and Trauma Findings : Examination Techniques, Clinical Evaluation, Clinical Presentation - Roth, Andreas (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book is a practical, step-by-step guide to orthopedic examination and diagnosis. The author explains a systematic classification of clinical findings that has proven very useful in diagnosing orthopedic disorders in daily routine. The approach to examination begins with a checklist covering the complete patient history, including subjective descriptions of complaints. This is followed by a stepwise approach to physical examination of the patient and collection of clinical findings. Photographs and illustrations clearly depict the necessary examination techniques. The main symptoms are then determined from the patient history and clinical findings, leading to a diagnosis. An overview of all relevant orthopedic conditions for each region of the body facilitates differential diagnosis and thereby completes the examination findings. This book will be of particular value for new residents in orthopedics and trauma but will also be useful for the experienced physician as a means of refreshing knowledge or as a reference.
Keywords: Medicine.; Orthopedics.; Rehabilitation.; Traumatology.; elektronické knihy; electronic books